SALT REVOLUTION: A SMART SOLUTION TO MEET THE NEEDS OF THE PETROLEUM INDUSTRY BY REFINING ROCK SALT THROUGH INNOVATIVE ABSTERSION METHODS - Hamzah Hamzah; Badrut Tamam Ibnu Ali; Dorit Bayu Islam Nuswantoro; Soleh Iskandar; Didi Dwi Anggoro; Budiyono Budiyono; Hens Saputra; Mochammad Ismail; Imam Wahyudi; Fausiah Fausiah; Aminuddin Aminuddin (Testing Center for Oil and Gas LEMIGAS, 2025)
The need for salt in the petroleum industry is very high, especially in drilling. This significant demand is not matched by salt production. Effective, low-cost, and environmentally friendly technology to produce salt of the appropriate quality is still a challenge in the petroleum industry. On the other hand, the amount of rock salt produced by salt farmers in Indonesia reaches 2.5 million tons per year. This research utilizes rock salt from salt farmers. It converts it into quality salt according to the needs of the petroleum industry by using a modified mixing washer method to increase NaCl purity and reduce impurity levels such as Ca2+ and Mg2+ ions. The results showed that rock salt was successfully converted into industrial-grade salt using the modified abstersion method with a mixer washer tool. The characteristics of the salt produced after the mixing washer are that it has a whiter and cleaner color than premium and rock salt. Mixer washer salt has a concentration of 98.80% NaCl, 0.064% Ca2+, and 0.062% Mg2+, meeting the standard for petroleum industry-grade salt and suitable for use in the drilling process.